Profile of tuberculosis among the foreign-born population in Japan, 2007–2014 - Lisa Kawatsu; Kazuhiro Uchimura; Kiyohiko Izumi; Akihiro Ohkado; Nobukatsu Ishikawa (Western Pacific Surveillance and Response, 2016)
The proportion of foreign-born people among the newly notified tuberculosis (TB) patients has been increasing in recent years and potentially poses a new challenge to TB control in Japan. In this report, we analysed the data from the Japan TB surveillance system between 2007 and 2014 to gain an overview of the trends and characteristics of foreign-born TB patients in Japan.